URGENSI PENDIDIKAN PROFETIK PADA ERA MILENIAL DALAM MENANGKAL FAHAM RADIKALISME DI PERGURUAN TINGGI ISLAM - Abidin, Zainal; Saadah, Tobibatussaadah (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UNSIQ Jawa Tengah, 2024)
This study aiming to expose about development movement radicalism among​ student in the modern era when entering the millennial era. This research is study qualitative with use method analysis document in various the source in the form of information from journals, book and actual news. In general line big results study show that; First, doctrine radical in the millennial era happen because socializing between fellow student and influence information from social media especially easy internet accessed and studied on sites that teach about views Islamic fundamentalists. Second in a way factual lots exposed students​ by understand radical originate from various campus college tall in a way easy infiltrated by influence movement fundamentalist or revivalist. Third, prophetic education is one alternative that can taught with carry out the learning process and introduce values of prophetic education that puts forward values humanity, tolerance, and moderation religion, diversity, and accommodation on every difference understand good that comes within the Muslim community as well as from abroad from people outside of Islam.